2005
DOI: 10.1063/1.1940119
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic activation in molecular beam epitaxy grown, in situ doped HgCdTe(211)

Abstract: Photovoltaic p-n junctions are the most significant active components of both current infrared photodetectors and advanced ones being developed. It is of the utmost importance to control both p- and n-type extrinsic doping. This letter addresses the issue of activating arsenic as a p-type dopant of Hg1−xCdxTe at temperatures sufficiently low that the integrity of p-n junctions and the intrinsic advantages of molecular beam epitaxy as a growth technique will not be compromised. The p-type activation of arsenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Similar results were obtained in all ranges of x values studied here, from x=0.2 to x=0.72. At arsenic doping levels above 10 18 cm -3 , lower activation ratios have been observed by other groups [18,19].…”
Section: Electrical Activitymentioning
confidence: 83%
See 1 more Smart Citation
“…Similar results were obtained in all ranges of x values studied here, from x=0.2 to x=0.72. At arsenic doping levels above 10 18 cm -3 , lower activation ratios have been observed by other groups [18,19].…”
Section: Electrical Activitymentioning
confidence: 83%
“…But in contrast to indium, which behaves very well as an n-type dopant, arsenic has amphoteric behavior and with typical MBE HgCdTe growth conditions is incorporated as an n-type dopant. This phenomenon has been seen by other groups and is still a source of discussion [15,[18][19][20][21]. One way to activate the arsenic as a p-type dopant is to anneal the layer under Hg pressure.…”
Section: Electrical Activitymentioning
confidence: 92%
“…At arsenic doping levels above 10 18 cm À3 , lower activation ratios have been observed by other groups. 18,19 CONCLUSIONS HgCdTe/Si has demonstrated very high potential as a cost-effective choice for producing large-area HgCdTe devices. Despite the large lattice mismatch between HgCdTe and Si, it is shown that HgCdTe layers can be obtained reproducibly with very high uniformity and quality.…”
Section: As Activitymentioning
confidence: 99%
“…This phenomenon has been seen by other groups and is still a source of discussion. 15,[18][19][20][21] One way to activate the arsenic as a p-type dopant is to anneal the layer under Hg pressure. Several works can be found in the literature modeling As activation 20,21 and detailing the procedure for annealing HgCdTe for this purpose 15,18-20 and will not be addressed in this work.…”
Section: As Activitymentioning
confidence: 99%
“…Whereas n-type doping using indium is well matured, the extrinsic p-type doping is still under development and usually requires thermal activation of column V elements. 6,7 Arsenic (As) is often chosen as the best candidate for both postgrowth ion implantation doping and in-situ incorporation. [8][9][10] This is for several reasons such as the low diffusion coefficient and the availability of mature molecular beam epitaxy (MBE) technology developed for the III-V industry.…”
Section: Introductionmentioning
confidence: 99%